베이나이트계 고강도강의 합금원소와 냉각조건이 미세조직, 인장성질, 충격성질에 미치는 영향 - 성효경; Hyo Kyung Sung; 신상용; Sang Yong Shin; 황병철; Byoung Chul Hwang; 이창길; Chang Gil Lee; 김낙준; Nack J. Kim; 이성학; Sung Hak Lee (대한금속·재료학회지, 48(9), 2010)
The effects of alloying elements and the cooling condition on the microstructure, tensile properties, and Charpy impact properties of high-strength bainitic steel plates fabricated by a controlled rolling process were investigated in the present study. Eight kinds of steel plates were fabricated by varying C, Cr, and Nb additions under two different cooling rates, and their microstructures and tensile and Charpy impact properties were evaluated. The microstructures present in the steels increased in the order of granular bainite, acicular ferrite, bainitic ferrite, and martensite as the carbon equivalent or cooling rate increased, which resulted in a decrease in the ductility and Charpy absorbed energy. The steels containing a considerable amount of bainitic ferrite or martensite showed very high strengths, together with good ductility and Charpy absorbed energy. In order to achieve the best combination of strength, ductility, and Charpy absorbed energy, granular bainite and acicular ferrite were properly included in the high-strength bainitic steels by controlling the carbon equivalent and cooling rate, while about 50 vol.% of bainitic ferrite or martensite was maintained to maintain the high strength.